(untitled) (ArtCultura, 2011)
O estudo analisa a imagem da criança na pintura e na fotograï¬a. As imagens de crianças sugerem um ensaio de modulação da afeccionalidade social sobre a infância, o que permite trabalhar com aspectos ainda pouco explorados, no que diz respeito à imagem de crianças. Na pintura e na fotografia crianças tornam-se anjos, meninas enlaçam-se e enlaçam a composição da obra, corpos repousam sobre lençóis, meninos transï¬guram a inquietude da puerícia. As paisagens são permeadas pelos enigmas da infância. As imagens da criança não são retratos de uma certa infância, o que faz a sua força é que elas são imagens políticas e inseparavelmente imagens de um inconsciente social, e sob esta ótica, são registros de corpos sempre falados, descritos e analisados por adultos, não tendo voz própria, sobre as formas como vêm sendo interpretados, expressos, percebidos. PALAVRAS-CHAVE: infância; fotograï¬a; arte; criança; imagem. ABSTRACT: This study analyses the image of children in the paintings and photography. The Children’s image insinuates a test of modulation of social aï¬€ ectionateness on infancy, which permits that lesser explored aspects may be treated in regard to the image of children. Children in paintings and photography become angels, little girls entwine themselves and become part of the composition of the painting, bodies lie on sheets, lit le boys transï¬ gure the turbulence of childhood. Landscapes are permeated with the enigmas of infancy. Children’s images are not portrayed with a deï¬ ned infancy. What gives them strength is that they are political images, and images that are inseparable from social unconsciousness. It is through this perspective that they are records of bodies that are always talked about, and described and analyzed by adults, without manifesting through their own voices in regard to the forms that are being interpreted, expressed, and perceived. KEYWORDS: keywords: childhood; photography; art; children; image.